After the Concert… Blackstock Band (Symphony in the Flint Hills, 2009)
Blackstock is the successor to the Blackbury Band, which has played for the Symphony after party for the past two years. It is named in honor of the Blackbury Band founder, Bob Black, who died in January 2009. Remaining members of the Blackbury Band decided to carry on the tradition so they can continue to entertain both their Symphony in the Flint Hills audience, as well as fans from other venues.
Keywords: art; band; music; jam groups; entertain; Classical; Guitar; folk; Symphony